Perceptions of hand hygiene amongst health care workers in Sibu, East Malaysia - Birks, Melanie Jane; Coyle, Meaghan; Porter, Joanne; Mills, Jane (International Journal of Infection Control, 2011)
The importance of hand hygiene in preventing the spread of disease is universally accepted. Nonetheless, many health care professionals, in spite of acknowledging the significance of this practice, are not always vigilant in carrying out hand hygiene. The purpose of this paper is to report on a study of the perceptions of health care workers in relation to hand hygiene. This study employed a quantitative survey design to ascertain the perceptions of hand hygiene amongst health care professions in the unique location of Sibu, East Malaysia. A modified World Health Organisation questionnaire was used to gather data that was subjected to descriptive analytical techniques. The outcomes of this research indicated that those sampled recognise the importance of performing hand hygiene both for themselves and others. Participants rated a number of activities as of particular value in promoting hand hygiene. The findings of this study reinforce much of the literature, particularly in relation to need for education, resources and supportive measures in ensuring good hand hygiene practices. Recommendations from this study suggest the need for future larger research studies that explore additional socio-cultural factors and employ more diverse methods to enhance the validity of the findings.